Effects of substrate availability on myocardial C-11 palmitate kinetics by positron emission tomography in normal subjects and patients with ventricular dysfunction - Schelbert, Heinrich R.; Henze, Eberhard; Sochor, Heinz; Grossman, Robert G.; Huang, Sung-Cheng; Barrio, Jorge R.; Schwaiger, Markus; Phelps, Michael E. (The American heart journal, 1986)
The possibility of demonstrating noninvasively with C-11 palmitate and positron emission tomography (PET) changes in myocardial substrate metabolism in normal and diseased human myocardium in response to altered substrate availability in blood and disease-related abnormalities was examined in five normal volunteers and 16 patients with ventricular dysfunction. C-11 palmitate injection and serial PET imaging were performed after an overnight fast (control period) and again 2 hours later after oral glucose (50 gm). Myocardial C-11 time-activity curves from serial PET images revealed a biexponential clearance pattern. An early rapid phase, defined by relative size and clearance half-time, reflects C-11 palmitate oxidation and the late slow phase tracer deposition in the endogenous lipid pool. During the control period, the tracer fraction entering the early rapid phase averaged 47 ± 13% (SD) in normal subjects and 45 ± 12% in patients. Corresponding clearance half-times were 19 ± 7 and 20 ± 5 minutes, respectively. Heart rate and blood pressure remained unchanged after glucose, but plasma glucose levels rose by 72.5% in normal subjects and by 98.9% in patients, while free fatty acid levels fell by 72% and 42% ( p < 0.001), respectively. In normal subjects, the tracer fraction in the early rapid phase fell by 43% ( p < 0.005) and the clearance half-time increased by 46% ( p < 0.01). In patients, the response of C-11 palmitate tissue kinetics to glucose was variable. In nine patients, it was similar to that in normal subjects while in the other seven patients a “paradoxic” response occurred. The tracer fraction entering the rapid clearance phase increased after glucose by 30% ( p < 0.05) associated with a 36% ( p < 0.05) decline in clearance half-times. The paradoxic response was unrelated to disease etiology or plasma substrate levels but occurred mostly in left ventricles with more severely depressed function. Thus, PET and C-11 palmitate allow the noninvasive demonstration of the known response of substrate metabolism of the human heart to altered substrate availability. Glucose administration in fasted humans serves as a provocative test of substrate regulation which can be abnormal in myocardial disease and can be demonstrated noninvasively.